The Effects of Green Accounting, Green Innovation, and Green Competitive Advantage on Sustainability Performance at Hotels In East Kalimantan - Haris Masri; Yana Ulfah; Fibriyani Nur Khairin (JURNAL ECONOMINA, 2026)
This study aims to analyze the effects of green accounting, green innovation, and green competitive advantage on sustainable performance in the hospitality industry in East Kalimantan Province. Using a quantitative approach, primary data were collected from the entire population of hotel managers in the region and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results of the study reveal that: (1) Green accounting has no significant effect on sustainability performance (P = 0.826), indicating that the allocation of environmental costs is still limited to short-term administrative compliance; (2) Green innovation has a positive and significant effect on sustainability performance (p = 0.000), proving that environmentally friendly product and process innovations are effective in reducing waste; (3) Green competitive advantage has a positive and significant effect and is the most dominant determinant of sustainability performance (p = 0.000, path coefficient = 0.628). The implications of this study confirm that hotel management must transform its ecological commitment into a market differentiation strategy in order to achieve holistic sustainability. Penelitian ini bertujuan untuk menganalisis pengaruh akuntansi hijau, inovasi hijau, dan keunggulan kompetitif hijau terhadap kinerja keberlanjutan di industri perhotelan di Provinsi Kalimantan Timur. Dengan menggunakan pendekatan kuantitatif, data primer dikumpulkan dari seluruh populasi manajer hotel di wilayah tersebut dan dianalisis menggunakan Pemodelan Persamaan Struktural berbasis Partial Least Squares (PLS-SEM). Hasil penelitian menunjukkan bahwa: (1) Akuntansi hijau tidak memiliki pengaruh signifikan terhadap kinerja keberlanjutan (P = 0,826), menunjukkan bahwa alokasi biaya lingkungan masih terbatas pada kepatuhan administratif jangka pendek; (2) Inovasi hijau memiliki pengaruh positif dan signifikan terhadap kinerja keberlanjutan (p = 0,000), membuktikan bahwa inovasi produk dan proses yang ramah lingkungan efektif dalam mengurangi limbah; (3) Keunggulan kompetitif hijau memiliki pengaruh positif dan signifikan serta merupakan penentu paling dominan terhadap kinerja keberlanjutan (p = 0,000, koefisien jalur = 0,628). Implikasi dari penelitian ini menegaskan bahwa manajemen hotel harus mengubah komitmen ekologisnya menjadi strategi diferensiasi pasar untuk mencapai keberlanjutan holistik.